Contextualization of Learning through Local Tourism Videos: A Quasi-Experimental Study on Descriptive Writing Skills - Handayani, Wuri; Suroso, Eko (Universitas Cokroaminoto Palopo, 2025)
This study aims to analyze the influence of the use of video tourism media on the ability to write descriptive texts of grade IX students of SMP Negeri 7 Cilacap. The method used was a quasi-experiment with two groups, namely the experimental group and the control group. The research instrument was in the form of a test to write descriptions given before (pretest) and after (posttest) treatment. The results of the prerequisite test showed that the data did not meet the assumptions of normality and homogeneity, so the analysis was continued with the non-parametric Wilcoxon Signed-Rank Test and the Mann-Whitney U Test. The results showed that there was a significant improvement in both groups, but the improvement in the experimental group was more consistent and substantial, with an average score increase of almost three times that of the control group. A more detailed analysis showed that the use of video media not only improved numerical scores, but also improved the quality of students' writing, especially in terms of content, text structure, and vocabulary. In addition, the use of local content in videos has been proven to make learning more contextual, relevant, and motivate students to write in more detail and sequence. Overall, this study emphasizes that video tourism media is an effective, adaptive, and sustainable learning strategy in developing description writing skills, and has the potential to be applied to various types of texts and other levels of education.